Dynamic interplay between diffusion and reaction: nitrogen recombination on Rh{211} in car exhaust catalysis. - Inderwildi, O; Jenkins, S; King, D (2008)
The adsorption and diffusion of atomic nitrogen on Rh{211} as well as formation and desorption of molecular nitrogen from this surface have been investigated by means of density functional theory (DFT) calculations. The elementary step reaction mechanism derived from this comprehensive DFT study forms the foundation of a detailed microkinetic model including diffusion, recombination, and desorption of nitrogen species. It will be shown that nitrogen formation on a stepped rhodium surface is a dynamic interplay of atomic nitrogen diffusion and reaction. Moreover, evidence will be presented that not one but several on-step recombination reactions are responsible for dinitrogen formation and desorption.